2016
DOI: 10.1016/j.nima.2016.03.057
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of antiprotons with the Timepix3 in a new electrostatic selection beamline

Abstract: a b s t r a c tWe present here the first results obtained employing the Timepix3 for the detection and tagging of annihilations of low energy antiprotons. The Timepix3 is a recently developed hybrid pixel detector with advanced Time-of-Arrival and Time-over-Threshold capabilities and has the potential of allowing precise kinetic energy measurements of low energy charged particles from their time of flight. The tagging of the characteristic antiproton annihilation signature, already studied by our group, is ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…3), both quantities are in close relation. For reasons of vividness and consistency with the notations used in other works [4,5] we prefer to use the term drift time t drift throughout the presented work.…”
Section: Correct For Possible Charge Losses By Dividing E Measi Bymentioning
confidence: 99%
See 2 more Smart Citations
“…3), both quantities are in close relation. For reasons of vividness and consistency with the notations used in other works [4,5] we prefer to use the term drift time t drift throughout the presented work.…”
Section: Correct For Possible Charge Losses By Dividing E Measi Bymentioning
confidence: 99%
“…Using a 1 mm thick CdTe at very low reverse bias of − 80 V, they achieved a z-resolution of 60 µm a e-mail: benedikt.bergmann@utef.cvut.cz (while the resolution in x and y was given by the pixel pitch of 110 µm). Turecek et al [3], Pacifico et al [4], and Bergmann et al [5] demonstrated and investigated the 3D track reconstruction capability of the latest generation of hybrid pixel detectors of the Medipix collaborations, Timepix3 [6], when used with a highly resistive planar silicon sensor. The latter has shown that a z-resolution of 29 µm can be achieved with a 500 µm thick silicon sensor layer at a bias voltage of 130 V.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detectors of the Timepix [2] technology have been employed in various applications, which include life science (imaging, hadron therapy, ...) [3,4], the measurement of angular correlation functions [5], space weather analyses [6], the determia e-mail: benedikt.bergmann@utef.cvut.cz nation of trapped particle directions in the radiation belts [7], or the study of the antiproton annihilation [8]. In particular Timepix detectors with a CdTe or CdZnTe sensor layer have been considered for double beta decay experiments [9].…”
Section: Introductionmentioning
confidence: 99%
“…The Timepix3 readout chip's improved time resolution and its capability of measuring the energy and time simultaneously in each pixel overcomes both issues. Turecek et al [11] and Pacifico et al [8] recently presented 3D reconstructions of particle trajectories with the Timepix3 readout chip attached to silicon sensors. It is the aim of the presented work to follow up on this by further improving and standardizing the methods for the z-reconstruction, and by presenting a detailed study of the achievable z-resolutions.…”
Section: Introductionmentioning
confidence: 99%